Silicon-carbon composite material as well as preparation method and application thereof
By covering the carbon layer and growing carbon nanotubes on the surface of the silicon carbon material, the problem of large volume changes and poor conductivity of the negative electrode material of silicon-based lithium-ion battery during charging and discharging is solved, and its electrochemical performance and Coulomb efficiency are significantly improved.
Patent Information
- Application Number
- CN202311135942.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
The negative electrode material of silicon-based lithium-ion battery has large volume changes, poor conductivity and poor electrochemical performance during charging and discharging, which limits its application in the field of energy storage.
By fully mixing the catalyst with the silicon carbon material, and using the rotary CVD method to coat the surface of the silicon carbon material with a uniform carbon layer and growing a certain amount of carbon nanotubes, a silicon carbon composite material with both a uniform carbon layer and a carbon nanotube coated on the surface was prepared.
The specific surface area and electrochemical impedance of silicon carbon materials are reduced, their electrochemical properties and first-time Coulomb efficiency are improved, and their buffering capacity for volume changes is enhanced.
Smart Images

Figure CN119560546A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite material, a preparation method and application thereof, and belongs to the technical field of energy storage materials. Background Art
[0002] With the rapid development of electric vehicles and 3C mobile electronic devices, lithium-ion batteries with advantages such as high energy density, low self-discharge, and long cycle life have attracted extensive attention from researchers. Graphite, as a common commercial negative electrode material, has advantages such as stable chemical properties, low charge and discharge potential platform, and no obvious volume expansion. However, the theoretical specific capacity of graphite is low, only 372mAh·g -1 Silicon-based negative electrode materials have an ultra-high theoretical specific capacity (e.g. the theoretical specific capacity of silicon is 4200mAh g -1 ) and a lower discharge platform (0.1V), it is expected to replace graphite as a new generation of commercial lithium-ion battery negative electrode material. However, due to the poor conductivity of silicon and the large amount of amorphous carbon in carbon materials, the impedance of the composite material is large, which reduces the electrochemical performance. Silicon-based negative electrode materials also have problems such as low conductivity and poor rate performance. At the same time, they will produce a large volume expansion during the charge and discharge process, resulting in the pulverization and shedding of electrode materials, limiting their application in the field of energy storage.
[0003] Nano-sizing silicon materials and compounding them with carbon materials is an important means to alleviate the large volume change of silicon during the charge and discharge process. However, the silicon-carbon materials reported in the prior art are generally spherical or irregular blocks, usually with a large specific surface area. During the first charge and discharge process, a large amount of SEI film will be produced, consuming electrolyte and reducing the first coulomb efficiency. At the same time, the conductivity of silicon-based materials is poor, resulting in large electrochemical impedance. Summary of the invention
[0004] In view of the problems of volume change and low conductivity of current silicon-based lithium-ion battery negative electrode materials during charging and discharging, the present invention provides a silicon-carbon composite material, a preparation method and application thereof. The catalyst is fully mixed with the silicon-carbon material, and a uniform carbon layer is coated on the surface of the silicon-carbon material by a rotary CVD method and a certain amount of carbon nanotubes are grown, so as to obtain a silicon-carbon composite material having both a uniform carbon layer and carbon nanotube coating on the surface. This not only reduces the specific surface area of the silicon-carbon material, but also can well reduce the impedance of the silicon-carbon material, thereby improving its electrochemical performance.
[0005] The technical solution adopted by the present invention is:
[0006] A silicon-carbon composite material comprises a silicon-carbon material, and a carbon layer and carbon nanotubes are coated on the surface of the silicon-carbon material.
[0007] The method for preparing the silicon-carbon composite material comprises the following steps:
[0008] S1: mixing the carbon tube catalyst with a solvent to obtain a catalytic solution;
[0009] S2: atomizing the catalytic solution and mixing it with silicon-carbon material powder to obtain a catalyst-mixed silicon-carbon material;
[0010] S3: Using a CVD rotary kiln, the catalyst mixed silicon-carbon material is heated in a nitrogen atmosphere, and then a mixture of nitrogen and low-carbon hydrocarbons is introduced. After cooling, a silicon-carbon composite material having a uniform carbon layer and carbon nanotubes coating on the surface is obtained.
[0011] Preferably, in step S1, the carbon tube catalyst is a transition metal catalyst, and the transition metal is any one of iron, nickel, cobalt, molybdenum and rubidium.
[0012] Preferably, in step S2, the mass ratio of the transition metal element in the catalytic solution to the silicon-carbon material powder is 10 -6 ~5×10 -5 :1.
[0013] Preferably, in step S2, the median particle size of the silicon-carbon material is 5-15 μm.
[0014] Preferably, in step S3, the heating temperature is 600-1200°C.
[0015] Preferably, in step S3, the low-carbon hydrocarbon is any one of methane, ethane, propane; ethylene, propylene; or acetylene and propyne.
[0016] Preferably, in step S3, the volume ratio of nitrogen to low-carbon hydrocarbons in the mixed gas is (0.5-5):1.
[0017] Preferably, in step S2, the catalytic solution and the silicon-carbon material are mixed in a mixer, and the mixer comprises:
[0018] The mixing tank is used to provide a space for mixing the catalytic solution and the silicon-carbon material. A liquid inlet pipe and a material feed pipe are respectively provided on both sides of the tank body;
[0019] An atomizer is installed at the front end of the liquid inlet pipe and is used to atomize the catalytic solution and spray it into the mixing tank;
[0020] A feeding pipe, connected to the feeding pipe, used to feed the silicon-carbon material into the feeding pipe;
[0021] A dust collector is installed at the front end of the feed pipe and is used to lift the silicon-carbon material fed into the feed pipe and send it to the mixing tank;
[0022] The pressure relief pipe is installed on the top of the mixing tank, and an automatic pressure relief valve is installed on the pipe body;
[0023] The discharge pipe is installed at the bottom of the mixing tank and is used to discharge the mixed materials. A discharge valve is installed on the pipe body.
[0024] The application of the silicon-carbon composite material in lithium-ion batteries refers to the use of the silicon-carbon composite material as the negative electrode material of the lithium-ion battery to prepare the negative electrode sheet. The specific method is to mix the silicon-carbon composite material and the binder in a mass ratio of (5-12): 1, add deionized water, and stir for 6-24 hours to obtain a suspension; then coat the suspension on a copper foil, vacuum dry it at 80-120°C for 10-20 hours, and then slice it to obtain the negative electrode sheet of the lithium-ion battery.
[0025] The present invention uses silicon-carbon material as a basic structural unit, fully mixes carbon tube catalyst particles with silicon-carbon material by a spray mixing method, and uses the mixed catalyst-mixed silicon-carbon material as a precursor, and finally obtains a silicon-carbon composite material with both a uniform carbon layer and carbon nanotube coating on the surface through carbon coating.
[0026] The inventors have found through research that after the carbon tube catalyst is mixed with the silicon-carbon material by the spray mixing method, and then carbon coating is performed by the CVD method, the carbon tube catalyst mixed in the silicon-carbon material can catalytically crack the carbon source and grow carbon nanotubes on the surface of the silicon-carbon material. The silicon-carbon composite material prepared by this method has a carbon layer coated on the surface of the silicon-carbon material, and a certain proportion of carbon nanotubes are compounded on the surface of the silicon-carbon material, which can not only reduce the specific surface area of the silicon-carbon material and improve the initial coulomb efficiency, but also can well reduce the impedance of the silicon-carbon material and improve its electrochemical performance. In addition, the carbon layer itself can also provide a buffer for the volume change of the silicon-based material during the charge and discharge process.
[0027] The beneficial effects of the present invention are:
[0028] 1. The present invention atomizes the solution containing the carbon tube catalyst into micron-sized droplets by spray mixing, and mixes the droplets with silicon-carbon material powder, so that the carbon tube catalyst can be evenly distributed on the surface of the silicon-carbon material;
[0029] 2. The present invention uses acetylene gas or the like as a carbon source and utilizes rotary CVD technology to coat the silicon-carbon material with a gas phase carbon source, which can make the thickness of the carbon coating layer more uniform;
[0030] 3. The CVD carbon coating process is carried out through a continuous CVD rotary kiln. The rotary motion of the equipment can make the negative electrode material powder contact with the carbon source cracking product more fully, so that more powder material can be coated;
[0031] 4. The volume ratio of acetylene to nitrogen in the acetylene and nitrogen mixed gas introduced into the CVD rotary kiln can be adjusted by a flow meter to facilitate the change of process parameters.
[0032] 5. Through the catalytic action of carbon tube catalyst, the carbon source is pyrolyzed at high temperature, and a certain number of carbon nanotubes and a carbon layer of a certain thickness are grown on the surface of the silicon-carbon material, and finally a carbon layer and carbon nanotube-coated lithium-ion battery negative electrode material is prepared; the first coulomb efficiency of the material can exceed 89%, and the electrochemical impedance is significantly reduced, which provides a theoretical basis for the commercial application of the material in the field of energy storage materials;
[0033] 6. The present invention can also control the electrochemical impedance of the silicon-carbon composite material by controlling the mass ratio of the carbon tube catalyst to the silicon-carbon material in the catalyst-mixed silicon-carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a scanning electron microscope image of the silicon-carbon composite material in Example 2;
[0035] Figure 2 It is a partial enlarged view of the scanning electron microscope image of the silicon-carbon composite material in Example 2;
[0036] Figure 3 The electrochemical impedance spectrum of the silicon-carbon composite material in Example 1, in which the control group material is silicon-carbon raw material;
[0037] Figure 4 This is the electrochemical impedance spectrum of the silicon-carbon composite material in Example 2, where the control group material is the silicon-carbon raw material;
[0038] Figure 5 This is the electrochemical impedance spectrum of the silicon-carbon composite material in Example 3, where the control group material is the silicon-carbon raw material;
[0039] Figure 6 The electrochemical impedance spectroscopy of the silicon-carbon composite material in Example 1 and Example 2, wherein the control group material is the silicon-carbon raw material;
[0040] Figure 7 The electrochemical impedance spectroscopy of the silicon-carbon composite material in Example 2 and Example 3, wherein the control group material is the silicon-carbon raw material;
[0041] Figure 8 The first charge-discharge capacity and voltage relationship curve of the silicon-carbon composite material in Example 1, in which the control group material is silicon-carbon raw material;
[0042] Fig. 9 The first charge-discharge capacity and voltage relationship curve of the silicon-carbon composite material in Example 1 and Example 2, in which the control group material is silicon-carbon raw material;
[0043] Fig.10 The first charge and discharge capacity and voltage relationship curves of the silicon-carbon composite materials in Examples 2 and 3, wherein the control group material is silicon-carbon raw material.
[0044] Fig.11 is a schematic diagram of the structure of the mixer;
[0045] The main reference numerals in the figure have the following meanings:
[0046] 1. Mixing tank, 2. Liquid inlet pipe, 3. Feed pipe, 4. Atomizer, 5. Feeding pipe, 6. Dust collector, 7. Discharge pipe, 8. Discharge valve, 9. Pressure relief pipe, 10. Automatic pressure relief valve. DETAILED DESCRIPTION
[0047] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.
[0048] Example 1
[0049] The present embodiment provides a method for preparing a silicon-carbon composite material, specifically: 10kg of silicon-carbon raw material is placed in the feed bin of a continuous CVD rotary kiln. Turn on the rotary motor and heating element of the continuous CVD rotary kiln to start heating, and set the frequency of the rotary motor to 50Hz. Set the working temperatures of the three temperature zones to 700℃, 800℃, and 900℃, respectively, and the heating rate to 150℃ / min. During the heating process, nitrogen is introduced to drive out oxygen, and the inlet flow rate of nitrogen is set to 8L / min. When the oxygen content drops below 50ppm and the temperature reaches the setting requirements, turn on the feed motor of the CVD rotary kiln and set the motor frequency to 25Hz. Half an hour later, turn on the acetylene pipeline switch, set the acetylene flow rate to 3L / min, and carbon-coat the silicon-carbon raw material. One hour after observing that the material in the feed bin is emptied, turn off the acetylene. The silicon-carbon composite material finally prepared is collected at the discharge port of the CVD rotary kiln.
[0050] The obtained silicon-carbon composite material and the binder (sodium carboxymethyl cellulose) were uniformly mixed at a mass ratio of 8:1 and 800 μL of deionized water was added, and stirred at room temperature for 12 hours; after stirring, the obtained suspension was evenly coated on the copper foil (the coating amount on each square centimeter of copper foil was about 1 mg), and vacuum dried at 100°C for 12 hours; the obtained electrode sheet was cut into a disc with a diameter of 12 mm using a manual slicer to obtain a negative electrode sheet. In this embodiment, the battery adopts a standard half-cell configuration, the battery shell is a CR2025 stainless steel button battery, the lithium sheet is used as the counter electrode, Celgard 2500 is used as the diaphragm, and the electrolyte is a mixed solution of 1M LiPF6 ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) (volume ratio 1:1:1). The voltage range of this test is 0.01~3V, and the test current is 0.2Ag -1 The test adopts LANDCT2001A battery test system.
[0051] Figure 3This is the electrochemical impedance spectrum of the silicon-carbon composite material in Example 1, and the control group material in the figure is silicon-carbon raw material. The semicircle diameter in the high-frequency region of the figure reflects the transfer impedance of the charge at the electrode interface, and the larger the diameter of the arc, the greater its impedance. It can be seen that the electrochemical impedance of the carbon-coated silicon-carbon composite material is lower than that of the silicon-carbon raw material that has not been carbon-coated.
[0052] Figure 8 The first charge-discharge capacity and voltage relationship curve of the silicon-carbon composite material in Example 1, in which the control group material is silicon-carbon raw material. It can be seen from the figure that the first coulomb efficiency of the obtained silicon-carbon composite material is 85.8%, the first coulomb efficiency of the silicon-carbon raw material is 81.7%, and the first coulomb efficiency of the silicon-carbon finished product after carbon coating is improved.
[0053] Example 2
[0054] This embodiment provides a mixer, see Fig.11 As shown, it specifically includes a mixing tank 1, which is used to provide a space for mixing the catalytic solution and the silicon-carbon material. A liquid inlet pipe 2 and a feed pipe 3 are respectively provided on both sides of the tank body; an atomizer 4 is installed at the front end of the liquid inlet pipe 2, which is used to atomize the catalytic solution and spray it into the mixing tank 1; the feed pipe 3 is connected to the feeding pipe 5, and the silicon-carbon material is fed into the feed pipe 3 through the feeding pipe 5, and a dust collector 6 is installed at the front end of the feed pipe 3 for lifting the silicon-carbon material fed into the feed pipe 3 and sending it to the mixing tank 1; the catalytic solution enters the mixing tank 1 in an atomized manner, and the silicon-carbon material enters the mixing tank 1 in a dusting manner, so that the carbon tube catalyst particles and the silicon-carbon material can be fully mixed; a discharge pipe 7 is installed at the bottom of the mixing tank 1, and a discharge valve 8 is installed on the pipe body, and the mixed material is discharged and collected through the discharge pipe 7. At the same time, in order to ensure the safety of the mixing tank 1, a pressure relief pipe 9 is also installed on the top of the mixing tank 1, and an automatic pressure relief valve 10 is installed on the pipe body.
[0055] This embodiment also provides a method for preparing a silicon-carbon composite material, specifically: 0.1 g of ferrocene powder and 50 mL of anhydrous ethanol are mixed, ultrasonically stirred at room temperature for 30 min to form an orange-red transparent solution, and the solution is placed in an atomizer at the liquid inlet end of a mixer, wherein the ferrocene powder is a catalyst. 10 kg of silicon-carbon raw material is added to the feed pipe of the mixer at intervals, and the silicon-carbon raw material is blown into the mixing tank with a dust collector while adding.
[0056] Set the spray particle diameter of the atomizer to <5μm, the compressed air flow rate of the atomizer to 5L / min, and the spray speed to 2mL / min. Set the air pressure of the dust collector to 1MPaG and the feed rate to 0.4kg / min. Turn on the power switch of the mixer to put it into working state. The working time of each working cycle of the atomizer and the dust collector is 3s. After the mixer works for 30 minutes, collect the catalyst mixed with silicon carbon raw materials in the discharge pipe of the mixer.
[0057] The remaining steps are the same as those in Example 1, except that the material put into the continuous CVD rotary kiln is replaced with the catalyst mixed silicon-carbon raw material collected at the discharge port of the mixer to finally obtain the silicon-carbon composite material.
[0058] Figure 1 is a scanning electron microscope image of the silicon-carbon composite material in Example 2, Figure 2 This is a partial magnified view of the scanning electron microscope image of the silicon-carbon composite material in Example 2. As can be seen from the image, a certain amount of carbon nanotubes grow on the surface of the silicon-carbon composite material.
[0059] Figure 4 This is the electrochemical impedance spectroscopy of the silicon-carbon composite material in Example 2. Figure 6 1 is the electrochemical impedance spectrum of the silicon-carbon composite material in Example 1 and Example 2. As can be seen from the figure, the electrochemical impedance of the silicon-carbon composite material in Example 2 is the lowest.
[0060] Fig. 9 The first charge-discharge capacity and voltage relationship curves of the silicon-carbon composite materials in Example 1 and Example 2. As can be seen from the figure, the first coulomb efficiency of the silicon-carbon composite material in Example 2 is 87%, which is higher than the silicon-carbon raw material and the silicon-carbon composite material in Example 1.
[0061] Example 3
[0062] This embodiment provides a method for preparing a silicon-carbon composite material. The specific steps are the same as those in Embodiment 2, except that the mass of the ferrocene catalyst is increased to 2 g. The remaining steps are the same as those in Embodiment 2, and finally a silicon-carbon composite material is obtained.
[0063] Figure 5 is the electrochemical impedance spectroscopy of the silicon-carbon composite material in Example 3, Figure 7 1 is the electrochemical impedance spectrum of the silicon-carbon composite material in Example 2 and Example 3. It can be seen from the figure that the electrochemical impedance of the silicon-carbon composite material in Example 3 is the lowest.
[0064] Fig.10 The first charge-discharge capacity and voltage relationship curves of the silicon-carbon composite materials in Example 2 and Example 3. As can be seen from the figure, the first coulomb efficiency of the silicon-carbon composite material in Example 3 is 89.6%, which is higher than the silicon-carbon raw material and the silicon finished material in Example 2.
[0065] From the above examples, it can be seen that the product of the present invention is to fully mix a small amount of carbon tube catalyst with powdered silicon-carbon raw material by spray mixing, and use CVD method to prepare carbon coating layer and carbon nanotubes on the surface of silicon-carbon raw material at the same time, and finally obtain silicon-carbon composite material. By adjusting the mass ratio of catalyst to silicon-carbon raw material, the electrochemical impedance and first coulomb efficiency of the finally obtained silicon-carbon composite material are changed regularly, so that the electrochemical performance of the silicon-carbon composite material is significantly improved.
[0066] Matters not covered by the present invention are known technologies.
[0067] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material comprises a silicon-carbon material, and a carbon layer and carbon nanotubes are coated on the surface of the silicon-carbon material.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The steps include: S1: mixing the carbon tube catalyst with a solvent to obtain a catalytic solution; S2: atomizing the catalytic solution and mixing it with silicon-carbon material powder to obtain a catalyst-mixed silicon-carbon material; S3: The catalyst-mixed silicon-carbon material is heated in a nitrogen atmosphere, and then a mixture of nitrogen and low-carbon hydrocarbons is introduced, and carbon coating is performed by CVD method. After completion, the material is cooled to obtain a silicon-carbon composite material having both a uniform carbon layer and carbon nanotube coating on the surface.
3. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S1, the carbon tube catalyst is a transition metal catalyst, and the transition metal is any one of iron, nickel, cobalt, molybdenum, and rubidium.
4. The method for preparing the silicon-carbon composite material according to claim 3, characterized in that: In step S2, the mass ratio of the transition metal element in the catalytic solution to the silicon-carbon material powder is 10 -6 ~5×10 -5 :
1.
5. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S2, the median particle size of the silicon-carbon material is 5-15 μm.
6. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S3, the heating temperature is 600-1200°C.
7. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S3, the low-carbon hydrocarbon is any one of methane, ethane, propane; ethylene, propylene; or acetylene and propyne.
8. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S3, the volume ratio of nitrogen to low-carbon hydrocarbons in the mixed gas is (0.5-5):
1.
9. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: In step S2, the catalytic solution and the silicon-carbon material are mixed in a mixer, and the mixer comprises: The mixing tank is used to provide a space for mixing the catalytic solution and the silicon-carbon material. A liquid inlet pipe and a material feed pipe are respectively provided on both sides of the tank body; An atomizer is installed at the front end of the liquid inlet pipe and is used to atomize the catalytic solution and spray it into the mixing tank; A feeding pipe, connected to the feeding pipe, used to feed the silicon-carbon material into the feeding pipe; A dust collector is installed at the front end of the feed pipe and is used to lift the silicon-carbon material fed into the feed pipe and send it to the mixing tank; The pressure relief pipe is installed on the top of the mixing tank, and an automatic pressure relief valve is installed on the pipe body; The discharge pipe is installed at the bottom of the mixing tank and is used to discharge the mixed materials. A discharge valve is installed on the pipe body.
10. Use of the silicon-carbon composite material according to claim 1 in a lithium-ion battery, characterized in that: A negative electrode sheet is prepared by using a silicon-carbon composite material as a negative electrode material for a lithium-ion battery. The specific method is to mix the silicon-carbon composite material and a binder in a mass ratio of (5-12):1, add deionized water, and stir for 6-24 hours to obtain a suspension; then, the suspension is coated on a copper foil, and vacuum dried at 80-120°C for 10-20 hours, and then sliced to obtain a negative electrode sheet for a lithium-ion battery.